Marginal Subjects : Gender and Deviance in Nineteenth Century Spain - Tsuchiya, Akiko, 1959- (Book collections on Project MUSE., 2011)
"Late nineteenth-century Spanish fiction is populated by adulteresses, prostitutes, seduced women, and emasculated men - indicating an almost obsessive interest in gender deviance. In Marginal Subjects, Akiko Tsuchiya shows how the figure of the deviant woman--and her counterpart, the feminized man - revealed the ambivalence of literary writers towards new methods of social control in Restoration Spain.